Can Augmented Reality Influence Consumer Responses? An Experiential Hierarchy Model Perspective - Vidyanata, Deandra; Gosal, Gladys Greselda; Subagio, Dyajeng Puteri Woro (Universitas Airlangga, 2025)
Objective: This study aims to examine how the key characteristics of Augmented Reality (AR) affect consumers’ psychological responses and purchase intention. Drawing on the Experiential Hierarchy Model, the research investigates sequential effects on affective (Flow), cognitive (Experience Satisfaction, Decision Comfort), and behavioral outcomes (Purchase Intention). Design/Methods/Approach: A quantitative post-treatment design was employed. Respondents (N = 400) interacted with AR-based try-on feature before completing a structured questionnaire. Purposive sampling ensured inclusion of individuals without prior purchase experience. Constructs were measured using established scales, and data were analyzed using PLS-SEM. Findings: Results show that AR characteristics significantly enhance flow and positively influences experience satisfaction and decision comfort. Both satisfaction and comfort strongly predict purchase intention, while flow itself does not exert a direct effect. Instead, mediation analysis confirmed that purchase intention is fully mediated by experience satisfaction and decision comfort, indicating that flow enhances purchase intention only through these evaluative pathways. Originality/Value: This study extends AR marketing literature by integrating four AR attributes within the Experiential Hierarchy Model, offering a holistic view of psychological pathways from AR experiences to consumer behavior. It advances understanding by introducing decision comfort alongside flow and satisfaction, applies the model to high-involvement product contexts, and contributes evidence from a developing country setting, thereby enhancing cross-cultural relevance. Practical/Policy implication: The findings indicate that AR influences purchase intention exclusively through satisfaction and decision comfort. Accordingly, managers are advised to conceptualize AR as a strategic decision-support mechanism. By enhancing realism, interactivity, and vividness, AR can reduce uncertainty, foster consumer confidence, and thereby facilitate more effective decision-making in high-involvement purchase contexts.